Keterwakilan Perempuan dalam Struktur Keorganisasian Mahasiswa - Muhammad Hafizh Aziz; Nadia Permata Sari; Dwi Putri Lestarika (CV. ITTC INDONESIA, 2024)
Women's representation in student organizational structures is an important issue that reflects the gender gap that still exists, even though the number of female students is often greater than male. This research uses normative juridical methods to explore the legal and social challenges that hinder women from occupying leadership positions in student organizations, such as gender stereotypes and lack of support from the social environment. The results of this research show that even though there are regulations that support gender equality, such as Law Number 39 of 1999 concerning Human Rights, practice in the field still shows the dominance of men in strategic positions. Therefore, it is important to increase women's representation so that student organizations can create more inclusive policies and encourage women's empowerment, so that they can form a future generation of leaders who value equality and social justice more.